ومضات تفريقية بين التورية والمشترك اللفظي والمجاز: Striking Differences between al-Tauriyah, al-Musytarak al-Lafẓī and al-Majāz - Ibrahim, Syazwan Naim; Pa, Mat Taib; Seman, Mohammad (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
ملخص التورية هي أن يذكر المتكلم لفظا له معنيان؛ معنى قريب غير مقصود ومعنى بعيد هو المقصود. لكن ثمة صعوبة والتباسا في فهم مفهوم التورية هذا لأن بعض البلاغيين يقحم مفهومي المشترك اللفظي والمجاز في التورية حتى يصعب التفريق بين تلك المفاهيم الثلاثة. لذا، يحاول البحث التأكد من مفهوم التورية والفرق بينها وبين المشترك اللفظي والمجاز. ومن ثم، وظف الباحثون مفهوم التورية للحموي (1894م) وفضل حسن عباس (2007م) لتحقيق ذلك الهدف. انتهج الباحثون المنهج الوصفي التحليلي بالرجوع إلى آراء البلاغيين القديمة والحديثة بغية تحقيق الهدف. وقد خلص الباحثون إلى أن التورية تتعامل مع معنيين حقيقيين؛ معنى قريب وبعيد وا لمجاز مع معنيين؛ معنى حقيقي ومجازي وهي تخفي الصلة بين معنييها وليس ذلك في المجاز. ثم كثرة تداول لفظ وقلته تلعب دورا في التورية لا في المجاز والمشترك اللفظي رافد التورية الأساسي. يوصي الباحثون في نهاية البحث بأن يجرى مزيد من بحوث تهتم بدراسة التورية. Abstract Al-Tauriyah is a single word uttered by a speaker that has two meanings; closer meaning that is not intended and distant meaning that is intended. However, there is a difficulty in understanding the concept of al-Tauriyah as some Arabic rhetoricians have treated the concept of al-Musytarak al-Lafẓī and al-Majāz as part of al-Tauriyah, leading to a difficulty in discerning between those concepts. Thus, the purpose of this study is to distinguish al-Tauriyah from al-Musytarak al-Lafẓī and al-Majāz. The researchers utilized al-Ḥamawī (1894M) and Faḍl Ḥasan ‘Abbās’s theory of al-Tauriyah (2007M) as a guidance to achieve the objective. The researchers employed a descriptive analytical method generally by referring to classical and modern scholarly opinions of Arabic rhetoricians which further support the theories to achieve the objective. The researchers concluded that al-Tauriyah deals with two real meanings; closer and distant meaning while al-Majāz deals with two meanings; real and metaphoric meaning, al-Tauriyah hides the relationship between its two meanings while al-Majāz does not, frequency of word use plays a role in al-Tauriyah and not in al-Majāz, and al-Musytarak al-Lafẓī is al-Tauriyah’s primary basis. The researchers hope that more research on al-Tauriyah will be carried out.